Expressive Speech Acts and Public Sentiments in Netizen Responses to Political Posts on X - Darmawan, Asy Syams Wahyu; Degaf, Agwin; Anggrisia, Nur Fitria (Universitas Pendidikan Mandalika, 2025)
The rise of online platforms like